Synergy Sources, Target Autonomy, and Integration in Acquisitions - Zaheer, Akbar; Castañer, Xavier; Souder, David (Journal of Management, 2013)
Determining the appropriate level of integration is crucial to realizing value from acquisitions. Most prior research assumes that higher integration implies the removal of autonomy from target managers, which in turn undermines the functioning of the target firm if it entails unfamiliar elements for the acquirer. Using a survey of 86 acquisitions to obtain the richness of detail necessary to distinguish integration from autonomy, the authors argue and find that integration and autonomy are not the opposite ends of a single continuum. Certain conditions (e.g., when complementarity rather than similarity is the primary source of synergy) lead to high levels of both integration and autonomy. In addition, similarity negatively moderates the relationship between complementarity and autonomy when the target offers both synergy sources. In contrast, similarity does not moderate the link between complementarity and integration. The authors’ findings advance scholarly understanding about the drivers of implementation strategy and in particular the different implementation strategies acquiring managers deploy when they attempt to leverage complementarities, similarities, or both.